2021
DOI: 10.1007/s10453-020-09681-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of indoor air quality in geriatric environments of southwestern Europe

Abstract: The objective of this study was to evaluate physical-chemical and microbial indicators of indoor air quality in three nursing houses (NHs) located in rural areas of the northeast of Portugal. The parameters were measured during two campaigns (winter and summer), twice a day, and in four distinct spaces for spatial variability assessment: dining room, living room, double bedroom and outdoor of the NHs. Physical-chemical indicators were assessed by using a Graywolf IQ 610 probe. Airborne microbial levels were ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…The dominant species were Gram-positive microbes. In field studies, Staphylococcus and Micrococcus appeared to be typical species in indoor air [ 21 , 25 ]. The bacteria found in the sampling were species that are commonly detected indoor air, such as Staphylococcus hominis (Gram-positive, the most important in terms of human health effects and the dominant species in universities [ 44 , 45 ]), Micrococcus yunnanensis (Gram-positive, found in the human skin microbiome [ 45 ]) and Microbacterium oleivorans (Gram-positive, identified in human clinical specimens [ 46 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant species were Gram-positive microbes. In field studies, Staphylococcus and Micrococcus appeared to be typical species in indoor air [ 21 , 25 ]. The bacteria found in the sampling were species that are commonly detected indoor air, such as Staphylococcus hominis (Gram-positive, the most important in terms of human health effects and the dominant species in universities [ 44 , 45 ]), Micrococcus yunnanensis (Gram-positive, found in the human skin microbiome [ 45 ]) and Microbacterium oleivorans (Gram-positive, identified in human clinical specimens [ 46 ]).…”
Section: Resultsmentioning
confidence: 99%
“…In the field of aerobiology, airborne microbial pollutants have been found to have negative effects on health and indoor air quality [ 22 , 23 ]. In field studies, the species of Micrococcus , Staphylococcus , Cladosporium , Penicillium and Aspergillus were detected in indoor environments [ 24 , 25 ]. Moreover, microbial hazards are not only closely related to concentration and species, but also to contact time (“exposure”).…”
Section: Introductionmentioning
confidence: 99%
“…For elderly centers, CO 2 is a popular parameter that has been included in most of the IAQ evaluations conducted. Results from these assessments show that indoor CO 2 concentrations above ASHRAE recommendations have been reported in the majority of the works [9,38,39,58,59], with a limited number of studies finding CO 2 levels below 1000 ppm [7,18]. In general, the authors justified the high concentrations found in their studies with the existence of insufficient ventilation rates and/or high occupancy density [9,18].…”
Section: Carbon Dioxidementioning
confidence: 86%
“…In fact, after a ventilation system renovation in Estonian nursing homes, Mikola et al [59] observed a remarkable reduction in indoor CO 2 levels, which complied with guidelines. Some authors reported the highest levels for bedrooms [9,38] and others for living rooms [39,58], drawing rooms [2], or dining rooms [2,58], with levels typically increasing during the afternoon period in areas where people stay for more time. Moreover, Mendes et al [2] observed differences in the CO 2 levels detected as a function of the existence of window sealants and of the type of sealants used, which will probably influence the infiltration rate of outdoor air and consequently have an effect on CO 2 levels.…”
Section: Carbon Dioxidementioning
confidence: 99%
“…Wide ranges of microbial concentrations and different biodiversity have been reported in indoor environments in previous studies. However, some genera appeared to be typical of indoor air such as Staphylococcus , Bacillus , Micrococcus , Cladosporium , Aspergillus , and Penicillium 1,9,10,11 . Several studies have shown the importance of the ventilation for air purification, improvement of air quality, and respiratory health 2,10,12,13 .…”
Section: Introductionmentioning
confidence: 99%